1. The Effect of The Mixture of Wheat Flour With Some Kind of Flour and The Amount of Eel Meat on Eel Nugget - Sari Minarti P.; Ismed Suhaidi; Herla Rusmarilin (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The aim of this research was to find the effect of addition of wheat flour with some kind of flour and the amount of eel meat on eel nugget. This research was an initial step to find the best quality of eel nugget. The research was conducted in April-May 2012 in the Laboratory of Food Technology, Faculty of Agriculture, USU, Medan, using a completely randomized design with two factors, i.e : the mixture of wheat flour with some kind of flour (T): (wheat:rice, wheat:corn, wheat:sago, wheat:mocaf) and the amount of eel meat (B): (60%, 65%, 70%, 75%). Parameters analyzed were moisture content, ash content, protein content, fat content, organoleptic values of color of frozen eel nugget, and organoleptic values of color,  flavour, taste, and texture of  fried eel nugget. The results showed that the effect of the mixture of wheat flour with some kind of flour had highly significant effect on ash content, protein content, organoleptic values of color,  flavour, taste, and texture of fried eel nugget. The amount of eel meat had highly significant effect on the moisture content, ash content, protein content, fat content, and organoleptic values of flavour, taste, and texture of fried eel nugget. Interaction of the  two factors had highly significant effect on the ash content, protein content, organoleptic values of color of frozen eel nugget, and organoleptic values of color,  taste, and texture of fried eel nugget but had no effect on moisture content, fat content, and organolaptic values of flavour of fried eel nugget. Substitution of wheat flour and sago flour and 75% eel meat  produced the best quality of eel nugget.